Creating sustainable competitive advantage in the hospitality industry through commercial friendships: connecting the host and guest on a social and emotional level - Sake Jan Velthuis (Research in Hospitality Management, 2022)
A large part of quality and competitive advantage in hospitality comes from friendly service. A lot of research in the hospitality industry is done from the viewpoint of management and aimed at how businesses should be designed to be friendly, yet little research is done into the perspective of the guest to show if the design works. This article tries to start the discussion and drive research towards a better understanding on how interaction between a host and a guest could lead to a concept called Commercial Friendship (CF), which comes from a connection on an emotional and personal level. CF is known to be beneficial to marketing investments, yet little research is done on friendship in marketing in general and even less in the hospitality industry in particular. This article puts forward a conceptual framework grounded in theory from hospitality, marketing, psychology and experience design. Research questions are given along with new ways to do research in hospitality design using a combination of verbal, behavioral and psychophysical measures.